Pengembangan Media Pembelajaran untuk Meningkatkan Kemampuan Lob dan Smash dalam Pembelajaran Bulutangkis - Sapto Adi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This study focused on developing media for teaching badminton intended to better students’ lobs and smashes. It involved 10 out of 34 students of Physical Education Department of State University of Malang. The development went through the stages of need analysis, media design, review by experts, media production, reviews and revision of the product, product trial, product revision, and final production. The study resulted in the teaching media in the forms of handles used to move shuttlecocks and support poles.